Exaggerated blood pressure response to static exercise in hindlimb ischemia-reperfusion - Qin, Lu; Li, Jianhua (Frontiers in Physiology, 2022)
Peripheral artery disease (PAD) reduces the blood flow supply in the affected limbs as one of the significant cardiovascular concerns. Revascularization surgery in the femoral artery plays a central role in treating PAD. Exercise is also a rehabilitation strategy suggested for PAD patients to improve vascular functions. However, the effects of limb ischemia-reperfusion (IR), one of the most predominant complications in revascularization surgery, on exercise-induced arterial blood pressure (BP) response are poorly understood. In the present study, we determined 1) the blood flow status in the hindlimb muscles of rats (plantar muscle, red and white portions of gastrocnemius) with different time points of the hindlimb IR; and 2) the BP response to static muscle contraction in rats at different time points after the blood flow reperfusion procedure. Results of this study indicated that, compared with the Sham group, the blood flow in the hindlimb muscles evaluated by Evans blue concentration was significantly reduced at 6 hours of femoral artery occlusion (FAO 6h) (vs. sham control, P <0.05). The decreased blood flow was gradually recovered after the blood flow reperfusion for 18 (IR 18h), 66 (IR 66h), and 114 (IR 114h) hours (P <0.05 vs. FAO 6h for all IR groups). The response of mean arterial pressure was 20±4 mmHg in Sham rats (n=7); 32±10 mmHg in IR 18h rats (n=10); 27±7 mmHg in IR 66h rats (n=13); 26±4 mmHg in IR 114h rats (n=9) (P <0.05 vs. Sham for all groups). No significant difference was observed in the peak-developed tension during muscle contraction among all the groups (P >0.05). In conclusion, static exercise-induced BP response is exaggerated following IR. Whereas the BP response is not statistically significant but tends to decrease with a prolonged IR time, the exaggerated BP response remains through time points from post-IR 18 hours to 114 hours.